Geolocation: A form of business control and power - Báez Laguna, Erika (Scientific journal of social studies, 2023)
This paper analyzes corporate geolocation in relation to the employer’s power of control and the fundamental rights of the employee. In this sense, the rise of new technologies has resulted in their widespread use by the employer in any medium that allows detailed monitoring of the activities carried out. For this reason, the application of geolocation by the employer is studied in contrast to the rights of privacy, dignity and data protection. In order to provide a solution, the Principle of proportionality is considered as a possible answer to the problem of weighing rights.